Explaining anomalies in intertemporal choice: A mental zooming theory - Stein Holden (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2014)
I present a theory that can explain hyperbolic discounting and magnitude effects in intertemporal choice. This approach builds on theories of narrow framing and reference dependence and expands these theories in a novel way by examining hidden mental zooming in base consumption adjustment in decisions regarding intertemporal prospects of varying magnitudes and time horizons. Data from a field experiment were used to assess the theory with an incentive-compatible multiple price list approach involving magnitude levels of 5x, 10x and 20x the basic magnitude level with time horizons of one, three, six and 12 months. Without zooming adjustments in base consumption, very strong hyperbolic and magnitude effects were found, and present bias could not explain the hyperbolic effects. The mental zooming model provides an effective rational explanation of what appear to be significant intertemporal anomalies in the data.
Keywords: C93; D03; D91; 330; Intertemporal choice; hyperbolic discountin; magnitude effects; mental zooming theory; field experiment